The Role of Sharjah Youth Shura Council in Empowering Emirati Youth Socially: A Field Study on a Sample of Sharjah Youth Shura Council Members During the Period 2005-2012 - Aljarwan, Omar; yaiche, Ouassila (Al-Adab Journal, 2025)
The study aimed to identify the role played by Sharjah Youth Shura Council in empowering Emirati youth socially, and to identify statistically significant differences in this role according to the variables of gender and session, in addition to presenting some proposals capable of developing the council's strategy in empowering Emirati youth socially in the future.To achieve this endeavor, the study adopted the social survey method by sample, and an electronic questionnaire was distributed to a random stratified sample of (90) members of the Sharjah Youth Shura Council during its four sessions extending from (2005-2012), and the results concluded that the Sharjah Youth Shura Council plays an effective role in empowering Emirati youth socially, through programs and activities that work to create a participatory environment that helps youth express their opinions and communicate them to the responsible authorities, which enhances the principle of community participation and supports community development. There are no statistically significant differences in this role that can be attributed to the variables of gender and term. The former council members who were interviewed recommended the need to develop the experience of the Sharjah Youth Shura Council by creating virtual youth platforms and updating the work mechanisms and objectives.